2014
DOI: 10.4103/0300-1652.137193
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of cervicovaginal and serum ferritin levels in midgestation time to predict spontaneous preterm delivery

Abstract: Background:The aim of this study was to determine diagnostic value of cervicovaginal ferretin and serum ferretin levels at midgestation time in predicting preterm delivery in singleton pregnancies.Patients and Methods:A diagnostic test study through a prospective cohort design was carried out on 300 singleton pregnant women in 2012. A blood sample was obtained from all the patients within 22-24 gestational weeks for laboratory assessment of serum ferretin, and cervicovaginal sample was also taken to assess cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…It was found that more than half (61%) patients were ≥ 2 (Multi gravida) and it was also observed by Broumand 8 . In another study Khan 9 observed multigravida was 58.1% in preterm labor.…”
Section: Discussionsupporting
confidence: 62%
“…It was found that more than half (61%) patients were ≥ 2 (Multi gravida) and it was also observed by Broumand 8 . In another study Khan 9 observed multigravida was 58.1% in preterm labor.…”
Section: Discussionsupporting
confidence: 62%
“…The precise mechanism by which ferritin contributes to disease is unclear, though. Ramsey et al (16) saw a significant association between elevated cervical ferritin levels and subsequent spontaneous preterm birth along with Broumand et al (17), who also investigated serum levels of ferritin. However, cervicovaginal ferritin correlated poorly with serum ferritin levels as well as serum inflammatory markers such as interleukin 6.…”
Section: Summary Of Main Findingsmentioning
confidence: 98%
“…Cervical ferritin levels had a weaker association with spontaneous preterm birth under 35 weeks and 37 weeks, suggesting that the correlation is higher in very early preterm delivery especially with serum ferritin. Broumand et al (17) analysed ferritin levels in the cervicovaginal fluid using a cervicovaginal swab and the serum levels of ferritin in 280 women between 22 and 24 weeks of gestation and classified subsequent deliveries prospectively into preterm deliveries (<37+0 weeks of gestation), early preterm deliveries (<34+0 weeks of gestation) and very early preterm deliveries (<32+0 weeks of gestation). The mean serum ferritin level was significantly lower in term deliveries versus early and very early preterm deliveries.…”
Section: Nitric Oxide Nitrate and Nitritementioning
confidence: 99%
“…Preterm delivery, as the precedent of prematurity, is generally referred to childbirth before 37 weeks of pregnancy. It is considered not only as a main cause of neonatal mortality, but also, as a risk factor of behavioral problems even later through the child's life [1]. Recent experimental and clinical evidence have revealed an association between intrauterine inflammatory processes and preterm delivery.…”
Section: Introductionmentioning
confidence: 99%